1981
DOI: 10.1139/z81-209
|View full text |Cite
|
Sign up to set email alerts
|

Food-collecting and waste-rejecting mechanisms in Glottidia pyramidata and the persistence of lingulacean inarticulate brachiopods in the fossil record

Abstract: Potentially inedible particles entering the mantle cavity of Glottidia pyramidata impinge on the frontal surfaces of ungrooved outer tentacles and are removed very efficiently by frontal cilia beating directly towards the exhalent aperture. Particles which settle out of the inhalent current are resuspended by cilia on the mantle ampullae. Edible material passing between the outer tentacles is captured by the combined action of laterofrontal cilia beating into the grooves and frontal cilia beating towards the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…27C) and Laqueus californianus (Gilmour 1978). Gilmour (1981) described the structure of the tentacles Note the lack of frontal cilia. The lateral 'pump' cilia on the 8 tentacles provide the power drawing the water (arrows) through the crown.…”
Section: Phoronids and Brachiopodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27C) and Laqueus californianus (Gilmour 1978). Gilmour (1981) described the structure of the tentacles Note the lack of frontal cilia. The lateral 'pump' cilia on the 8 tentacles provide the power drawing the water (arrows) through the crown.…”
Section: Phoronids and Brachiopodsmentioning
confidence: 99%
“…Captured particles are transported down the grooves in water currents generated by the frontal cilia and the 'immobile' laterofrontal cilia are surrounded by rings of microvilli and have long rootlets extending deeply into the cytoplasm. The laterofrontal cells make synapse with the nervous system, and therefore Gilmour (1981) suggested that the stiff laterofrontal cilia may serve as sensory detectors of particles. More recently, Strathmann (2005) observed that larvae of G. pyramidata retain food particles on the frontal side of the tentacles by means of a sieve composed of a row of stationary laterofrontal cilia.…”
Section: Phoronids and Brachiopodsmentioning
confidence: 99%
“…The present description of the catch-up principle further substantiates the hypothesis proposed by Strathmann and Leise (1979), who found that suspended particles are concentrated when they are ''overtaken'' by cilia in their effective stroke and ''pushed faster than the water.'' Ciliary upstream-collecting animals possess ciliary bands that divert suspended food particles from the main water current and concentrate them on the upstream side of the band (Bullivant 1968a;Strathmann 1971Strathmann , 1973Strathmann and Bonar 1976;Gilmour 1979Gilmour , 1982Gilmour , 1985Nielsen 1987Hart 1990Hart , 1991Hart and Strathmann 1994; for review, see Nielsen and Riisgård 1998). The capture mechanism is correlated with the presence of a single band of cilia, which appears to be responsible for both the water transport and particle retention.…”
Section: Capture Mechanismsmentioning
confidence: 99%
“…Suspension feeding by planktonic larvae of echinoderms has been described by several workers (Strathmann 1971(Strathmann , 1975Strathman et al 1972;Gilmour 1985Gilmour , 1986Gilmour , 1988aHart 1991). Early workers offered divergent opinion about the mechanism by which these larvae capture suspended food particles from the seawater, but apparently many of the conflicting descriptions were resolved by Strathmann (1971), Strathmann et al (1972), andHart (1991).…”
Section: Capture Mechanismsmentioning
confidence: 99%
“…The tentacles of both larvae and adults are ciliated and form an upstream collecting system. Atkins (1958), Storch & Welsch (1976 and Reed & Cloney (1977) stated that there is one cilium per cell in all the ciliary tracts, while Gilmour (1978Gilmour ( , 1981 reported that the lateral and frontal cells of Laqueus and Glottidia are multiciliate. My transmission electron micrographs of tangential sections of tentacles of Crania, Discinisca, Lingula and Terebratulina clearly show that all cells are monociliate.…”
Section: Brachia Tamentioning
confidence: 99%